Water table fluctuation method to estimate the recharge of the free aquifer in the Guariroba river basin, Campo Grande – MS - Russi, Daniel; Lastoria, Giancarlo; Cavazzana, Guilherme Henrique; Gabas, Sandra Garcia; Oliva, Andressa (Ciência e Natura, 2021)
The Guariroba river basin was decreed as an Environmental Protection Area (EPA), and with a surface of 360 km² it is of great importance to the municipality of Campo Grande because it supports almost half of the water supply system of the latter. The surface of the basin is predominantly covered by Cretaceous sediments of the Caiuá Group, which constitutes the free aquifer known as the Bauru Aquifer System (BAS). Recent studies have confirmed the contribution of the BAS in the maintenance of the base flow of surface drainage. Therefore, the quantification of groundwater recharge (GWR) becomes fundamental. This work used the water table fluctuation (WTF) method, based on variations in the piezometric surface-water measurement, to estimate the GWR of the basin. From Mar 2015–Feb 2017, monthly variations of the static level were registered in 13 tubular wells located in the Guariroba EPA. Considering a 1480 mm annual precipitation, the estimated average GWR was 356 mm⋅year–1, varying between 210–694 mm⋅year–1. Despite considering a lower value of the effective porosity parameter (Sy = 0.1) than the one suggested for the BAS, the estimated average GWR-to-precipitation ratio (24%) was more than double that the one adopted by the state environmental agency (10%).